An Ethnoscience Study on The Making of Pandan Mats as Science Learning Resources - Garung, Etheldreda Rosari; Kerans, Geterudis; Ngongo, Febriani (FKIP ULM, 2024)
This study aimed to implement ethnoscience in analyzing pandan mat making in Wewewa Tengah and evaluating its implication as a learning source in science education. This research focused on studying the pandan mat-making process in Wee Patando Village and identifying its scientific contributions to traditional practice. Applying a qualitative research method, the data were collected through observation, interviews, and documentation. Meanwhile, the research instruments used are observation sheets, interview guides, and documentation. The data were analyzed through several stages: reduction, data presentation, and conclusion drawing. The results reveal that the pandan mat-making process involves several stages, including collecting pandan leaves, sorting, removing its thorns, drying, ware (scraping), rolling, tirri (dividing), weaving, melekuk (locking), and dumbi (placing pandan). The main challenge is in the drying process of pandan, which is affected by high humidity during the rainy season and may impact the quality of the mats. This study's contribution lies in applying scientific concepts to the traditional pandan mat-making process, such as plant physiology, the leaf structure and its function, the physical properties of materials, and principles of heat transfer and friction. The findings emphasize that the pandan mat-making process can serve as a concrete example for understanding science subjects, particularly in plant physiology and material physics. In science education, this research recommends integrating ethnoscience knowledge from pandan mat-making into the curriculum to enrich students' learning experiences. By understanding how scientific concepts are applied in traditional practices, students can see the relevance of science in daily life and enhance their comprehension of academic material through concrete and relevant examples.